(untitled) (Research, Society and Development, 2022)
In view of the reality established by the COVID-19 pandemic, online nutritional assistance was granted by the CFN to provide nutritional support. Thus, this study aimed to point out perceptions about nutrition teleconsultation, discussing the assessment, nutritional diagnosis, challenges and advantages of this method of care. It refers to a scientific literature review research, in which it was elaborated through a bibliographic survey in databases, with 8 scientific articles being included after applying the exclusion criteria. In view of the nutritionists’ reports, anthropometry, contact with the patient and technical difficulties are the most affected points in teleservice. Furthermore, problems with internet access in some regions, incompatible camera, lack of understanding of the technology, concerns about safety or preference for face-to-face nutritional monitoring were limitations presented by the patients. Despite this, the professionals indicated that they were satisfied with the method of care, reporting that it was an excellent choice during the pandemic, and that it should remain a complementary way to face-to-face consultations.